“Decoding” Policy Perspectives: Structural Topic Modeling of European Central Bankers’ Speeches - Warin, Thierry; Stojkov, Aleksandar (Journal of risk and financial management, 2023)
This research analyzes the speeches and interviews of high-level European Central Bank decision makers from 1997 to 2021 to identify clusters of prominent topics. Transparency is a crucial aspect of modern monetary policy, and public speeches and interviews by central bankers play a vital role in achieving it. Our study employs structural topic modeling to compare the prevalence of topics during the Global Financial Crisis, pandemic crisis, and periods of heightened inflation. Additionally, we explore the impact of central bank independence on official rhetoric.